Topological classification of (n−1)-convex sets - Mel’nik, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the properties of (n−1)-convex sets associated with the properties of conjugate sets. We give a complete topological classification of (n−1)-convex sets.